Poisoning in children and adolescents notified at a toxicology center in the Northeast of Brazil - Maria Lucineide Porto Amorim; Maria Júlia Gonçalves de Mello; Marília Teixeira de Siqueira
Abstract Objective: to analyze the clinical and epidemiological profile of poisoning in children and adolescents under 12years old. Methods: a crosssectional study with analytical component based on poisoning notifications at the Centro de Toxicologia de Pernambuco (Toxicological Center in Pernambuco), carried out in 2012 and 2014. Allergic reactions and contaminated food poisoning were excluded. Sociodemographic characteristics, type of toxic agent, circumstance, place of occurrence, time until care and patients' evolution were analyzed. The distribution of frequencies and associations among the variables through prevalence ratio and the chisquared test was determined. Results: Among 2,843 patients registered, 1,601 (56.3%) were poisoned by chemical substances and 1,242 (43.7%) by poisonous animals. Most lived in urban areas (90.6%) and were attended for care after an hour of the incident (47.6%). The poisoning frequency of chemical substances was higher among children under five years old (PR=2.34; CI95%= 2.142.56) and there was no difference in the sexes (PR=1.00; CI95%= 0.941.07). The predominant medicine (45.0%) for poisoning was between chemical substance and scorpions (77.0%). Poisoning occurred as accidental in 92.2% and 99.6% of chemical substance occurred at home. There were six deaths by chemical intake and two by scorpions.. Conclusions: poisoning in Pernambuco State is considered a public health issue given by its frequency and it occurred mostly with children under 5 years old accidentally and at home.